Micropropagação de bananeiras, detecção e identificação sorológica e molecular do Cucumber mosaic virus e do Banana streak virus - Carnelossi, Patrícia Rosin (2013)
The objective of this study was to standardize a method for in vitro multiplication of banana seedlings, and indexing for Cucumber mosaic virus (CMV) and Banana streak virus (BSV) through serological DAS-ELISA tests. Both virus were also detect by PCR, on samples taken from production areas of northern Paraná, seeking partial molecular characterization of viral isolates. The in vitro micropropagation of Cavendish bananas resulted in the production of 3653 seedlings from 151 gems, and the highest production was obtained with the rhizomes from tillers measuring 20-60 cm. The CMV and BSV were detected from plant samples collected in banana growing areas, as in 47% of the 53 plants obtained by micropropagation. Sequencing of the amplification product obtained by RT-PCR allowed the classification of the CMV isolate in the subgroup IA. The rolling circle amplification (RCA) used in protocols for detection of BSV episomal forms resulted in the amplification of approximately 7,5 Kbp. After partial sequencing of the RCA product and comparisons with sequences of BSV deposited in GenBank, the virus isolate from Andirá was identified as a species of Banana streak virus Obino I'Ewai (BSOLV) with 99% homology.This work indicated that CMV and BSV were found in single and in mixed infections in production áreas of northern Paraná, evidencing the importance of viral indexing for the fitossanitary quality of banana produced in this region.